2008
DOI: 10.1242/dev.016576
|View full text |Cite
|
Sign up to set email alerts
|

Tbx2b is required for the development of the parapineal organ

Abstract: Structural differences between the left and right sides of the brain exist throughout the vertebrate lineage. By studying the zebrafish pineal complex, which exhibits notable asymmetries, both the genes and the cell movements that result in left-right differences can be characterized. The pineal complex consists of the midline pineal organ and the left-sided parapineal organ. The parapineal is responsible for instructing the asymmetric architecture of the bilateral habenulae, the brain nuclei that flank the pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(120 citation statements)
references
References 56 publications
4
116
0
Order By: Relevance
“…The lor p25bbtl phenotype demonstrates many features opposite to those observed in enhanced S-cone syndrome and mutations of Nr2e3 or Nrl in mice. Genetic analysis revealed that lor p25bbtl is an allele of tbx2b, a T-box TF with essential roles in development (19)(20)(21)(22). Our data suggest that during photoreceptor cell differentiation, tbx2b acts cell-autonomously to promote the UV-cone fate by repressing the rod fate in zebrafish photoreceptor cell progenitors.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The lor p25bbtl phenotype demonstrates many features opposite to those observed in enhanced S-cone syndrome and mutations of Nr2e3 or Nrl in mice. Genetic analysis revealed that lor p25bbtl is an allele of tbx2b, a T-box TF with essential roles in development (19)(20)(21)(22). Our data suggest that during photoreceptor cell differentiation, tbx2b acts cell-autonomously to promote the UV-cone fate by repressing the rod fate in zebrafish photoreceptor cell progenitors.…”
mentioning
confidence: 72%
“…1G), where tbx4 and tbx2b/fby were localized (21). tbx2b is a TF mainly associated with transcriptional repression during cell cycle control, limb, heart and endoderm development (19,20,22), and cancer (25).…”
Section: Resultsmentioning
confidence: 99%
“…In the catshark, nodal inhibition through pharmacological treatment using the nodal antagonist SB-505124 leads to the loss of ScPitx2 transcripts specifically in the LPM, when injections are performed at stages [13][14], that is, before nodal expression in the LPM (Supplementary Table 3; compare Fig. 1s,t).…”
Section: Conserved Diencephalic Molecular Asymmetries In Vertebratesmentioning
confidence: 99%
“…The role of nodal is to control asymmetry laterality rather than its establishment per se, as abrogation of nodal signalling results in the randomization of habenular asymmetry rather than its total loss 10,11 . In addition, Fgf8-dependent lateralized migration of the parapineal rudiment plays a key part in the establishment of proper habenular asymmetries, as shown by the right isomerism phenotype observed following parapineal laser ablation or in zebrafish mutants exhibiting parapineal migration or specification defects [12][13][14] . Whether these mechanisms have been conserved throughout vertebrate evolution remains unclear.…”
mentioning
confidence: 99%
“…The mechanisms involved in the early asymmetric positioning of the PpO are currently unknown, although evidence suggests that PpO asymmetric morphogenesis involves the movement of a midline-unpaired structure that organizes as a cohesive rosette-like structure [40,59] that can form a cellular stream [60]. From the genetic perspective, PpO asymmetric migration requires the concerted activity of fibroblast growth factor (FGF) and Nodal signalling pathways.…”
Section: Nodal As Laterality Modulator In Midlineunpaired Structuresmentioning
confidence: 99%